Hot Deformation Characteristics and Processing Map of 1Cr12Ni2Mo2WVNb Martensitic Stainless Steel. Issue 7 (4th May 2020) - Zhao, Chao; Zhang, Jin; Yang, Bing; Li, Yi Fei; Huang, Jin Feng; Lian, Yong
Abstract : Herein, the hot deformation behavior of 1Cr12Ni2Mo2WVNb martensitic stainless steel is investigated through the high‐temperature thermal compression test. Meanwhile, a strain‐compensated Arrhenius constitutive equation is established. The correlation coefficient R between the predicted value and the experimental value is 0.994, and the average absolute relative error (AARE) (%) value is calculated to be 3.7845%. These results show that the improved constitutive model of 1Cr12Ni2Mo2WVNb steel achieves a higher accuracy in predicting the flow stress value. Moreover, the equation regarding the peak stress (strain), the critical stress (strain), and the Zener–Holomon parameter is constructed, which exhibits good linearity. In addition, the hot processing maps of 1Cr12Ni2Mo2WVNb steel under the strains of 0.3, 0.4, 0.5, and 0.6 are also established, respectively, based on the compression test. According to the processing map and microstructural observation, it is concluded that the optimal processing conditions for 1Cr12Ni2Mo2WVNb steel are determined as follows: a temperature of 1070–1100 °C, a strain rate of 0.8–1 s −1, and a peak power dissipation efficiency of about 0.34. Abstract : The correlation coefficient R and the average absolute relative error (AARE) (%) value were 0.994 and 3.7845%, respectively. These results show that the improved constitutive model of 1Cr12Ni2Mo2WVNb steel accurately predicts the flow stress value. The optimal processing conditions for 1Cr12Ni2Mo2WVNb steel are determined as follows: the temperature of 1070–1100 °C and the strain rate of 0.8–1 s −1 .